Biological Functions and Clinical Significance of the ABCG1 Transporter - Stanislav Kotlyarov; Anna Kotlyarova (Biology)
ATP-binding cassette (ABC) transporters are a large family of proteins that transport various substances across cell membranes using energy from ATP hydrolysis. ATP-binding cassette sub-family G member 1 (ABCG1) is a member of the ABCG subfamily of transporters and performs many important functions, such as the export of cholesterol and some other lipids across the membranes of various cells. Cholesterol transport is the mechanism that links metabolism and the innate immune system. Due to its lipid transport function, ABCG1 may contribute to the prevention of atherosclerosis and is involved in the functioning of the lung, pancreas, and other organs and systems. However, the full clinical significance of ABCG1 is still unknown and is a promising area for future research.